Business strategy in a semiglobal economy - Mourdoukoutas, Panos (M.E. Sharpe, 2006)
Provides both theory and strategy for operating in a semiglobal economy in which international businesses need to compete in highly globalized and highly localized markets at the same time. This book raises important challenges to the conventional models of business organization and the competitive strategies that proceed from them.